1979
DOI: 10.1007/bf00431995
|View full text |Cite
|
Sign up to set email alerts
|

The effect of housing and gender on preference for morphine-sucrose solutions in rats

Abstract: To determine whether opiate consumption is affected by laboratory housing, individually caged and colony rats were given a choice between water and progressively more palatable morphine-sucrose solutions. The isolated rats drank significantly more of the opiate solution, and females drank significantly more than males. In the experimental phase during which morphine-sucrose solution consumption was greatest, the isolated females drank five times as much, and the isolated males sixteen times as much morphine (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
3

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 21 publications
3
47
1
3
Order By: Relevance
“…These results seem, at first sight, contradictory with those of other authors (Alexander et al 1978 ;Hadaway et al 1979;Schenk et al 1987;Consorti et al 1992), showing that isolated rats self-administer or drink more morphine (or of other substances of abuse) than nonisolated animals. However, this contradiction may be only apparent.…”
Section: Discussioncontrasting
confidence: 80%
“…These results seem, at first sight, contradictory with those of other authors (Alexander et al 1978 ;Hadaway et al 1979;Schenk et al 1987;Consorti et al 1992), showing that isolated rats self-administer or drink more morphine (or of other substances of abuse) than nonisolated animals. However, this contradiction may be only apparent.…”
Section: Discussioncontrasting
confidence: 80%
“…Experimental studies have shown that although a higher vulnerability to drug intake is spontaneously observed in certain individuals, it can also be induced by life events and, in particular, by stress. For example, in the rat, only some subjects spontaneously develop amphetamine self-administration (Piazza et al, 1989(Piazza et al, , 1990b, whereas this behavior is enhanced by conditions such as social isolation (Alexander et al, 1978;Hadaway et al, 1979;Schenk et al, 1987;Bozarth et al, 1989), competition in the colony (Maccari et al,199 l), immobilization (Deroche et al, 1992b;Shaham et al, 1992) repeated tail pinch (Piazza et al, 1990a), and prenatal stress (Deminiere et al, 1992). Individual vulnerability and stress-induced predisposition to drug intake are associated with an enhanced locomotor response to psychostimulants, opioids, and novelty (Piazza et al, 1989(Piazza et al, , 1990aHooks et al, 1991;Deroche et al, 1992a), as shown also by the increase in addictive properties of drugs observed when the locomotor effects of psychostimulants and opioids are sensitized (Lett, 1989;Piazza et al, 1990a;Gaiardi et al, 199 1;Horger et al, 199 1) by their repeated injections (for review, see Robinson and Becker, 1986;Kalivas and Stewart, 1991).…”
Section: Studies Of Intravenousmentioning
confidence: 99%
“…Investigating environmental effects on morphine selfadministration in rats, we found that females consumed more morphine/sucrose solution than males (e.g. Hadaway et al 1979). Eriksson and KAianmaa (1971) reported that female C57BL mice consumed more unadulterated morphine solution than males but did not examine the effects of sweetening the solutions; nor did they compare DBAs of either sex.…”
mentioning
confidence: 99%